Correlations Between Mandibular Third Molars to Inferior Alveolar Nerve Locations in Vietnamese Population - Pham Ngoc Anh Thu; Tran Nhut Thao Trang; Florenly; Novelya (Biomedical Journal of Indonesia, 2021)
One of the probable complications in mandibular third molar extraction is thedamage to the inferior alveolar nerve (IAN). Calculating the distance between IANand third mandibular can decrease the complication risk. In this study, cone beamcomputed tomography (CBCT) scans were used to evaluate several factors relatedto the positional relationship between mandibular third molar and IAN in theVietnamese population. One-hundred-seventy-eight CBCT scans were collectedfrom dental clinics at Ho Chi Minh City, from 1st January 2018 to 28th February2021. Only 100 scans were included in this study, 55 scans of female and 45 scansof male patients. The age of the patients ranged from 19 to 59 years old. From thisstudy, the most common location of IAN relative to the roots of the mandibularthird molar was on the apical side (60.5%), followed by the buccal side (21.5%), thelingual side (16%), and the least common located between the roots (2%). Overall,the mean distance between mandibular third molar roots to IAN was 3.19Â±1.85mm. There was a significant correlation between the left and right sides ofthe IAN location, indicating symmetry. Moreover, there is no association was foundbetween gender and the location of IAN